PENGARUH RETURN ON ASSET, RETURN ON EQUITY, DAN EARNINGS PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI 2020-2022 - Borolla, Bretmy; Gasperz, Jefry; Layn, Yuyun Yuniarti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to empirically examine the return on assets, return on equity, and earnings per share of share prices of banking companieslisted in BEI 2020-2022. The method used in this study is quantitative methods. The population in this study is banking companies listed on the Indonesia Stock Exchange in the 2020-2022 period totaling 46 companies. With purposive samples, a sample of 34 companies was obtained with a total of 102 observations. The analytical tool used in this study is multiple linear regression analysis. The results of this study show that Return On Assets (ROA) has a significant positive effect on stock prices. Return On Equity (ROE) has a significant positive effect on stock prices. And Earnings Per Share (EPS) has a significant positive effect on stock prices